An ecological assessment of neighborhood, family, peer, and individual characteristics in predicting violence: a multilevel analysis of African-American families - Stewart, Eric Allen (2000)
This study used epidemic, cultural deviance, and social learning perspectives to examine the extent to which exposure to various forms of violence predicted violent behavior among 867 African-American youth. The study examined the following macro-level predictors of childhood violence: neighborhood violence, neighborhood SES, neighborhood subculture of violence, and percent African American. The following micro-level predictors were examined: street code, associating with violent peers, corporal punishment, parental violence, and warm/supportive parenting. Using hierarchical linear modeling techniques (HLM), the results showed that neighborhood SES was the only macro-level variable to exert a significant influence on violence. Furthermore, childhood violence was significantly related to street code, violent peers, parental violent behavior, and warm/supportive parenting. Overall, the results indicated that micro-level variables explained 27% of the variance, and macro-level variables explained an additional 3%. These findings demonstrate the importance of micro-level factors in predicting violence. It was concluded that simply living in a violent neighborhood does not produce violent children, but that family, peer, and individual characteristics at the micro-level play a large role in predicting violence in children